An exploration of the therapeutic alliance within a telephone‐based cognitive behaviour therapy for individuals with experience of psychosis. (26th January 2014) - Mulligan, John; Haddock, Gillian; Hartley, Samantha; Davies, Josie; Sharp, Tom; Kelly, James; Neil, Sandra T.; Taylor, Chris D.J.; Welford, Mary; Price, Jason; Rivers, Zoe; Barrowclough, Christine
<x xml:space="preserve">Abstract</x> Objectives This study investigated the therapeutic alliance (TA) between clients and therapists involved in a telephone‐based cognitive behaviour therapy (CBT) oriented psychological intervention for individuals experiencing psychosis. Design The telephone intervention involved recovery‐focused CBT with use of a self‐help guide and group intervention co‐facilitated by colleagues with personal experience of psychosis. It was delivered as part of a Participant Preference Trial. Methods Twenty‐one client/therapist dyads were examined within this study. In addition to a measure of TA, clients completed measures of depression, social functioning, symptom severity, and strength of treatment preference, while therapists completed measures related to the level of shared formulation, therapist confidence, and therapeutic change estimates. Results Therapeutic alliance levels were comparable to previously reported face‐to‐face psychosis intervention studies. Clients consistently reported significantly higher TA ratings compared to therapists. Depression scores and the strength of preference for treatment were significantly associated with client TA. Greater therapist perceived change was associated with higher therapist rated TA, while higher numbers of missed therapy sessions associated with lower therapist ratings. Conclusions Telephone‐based psychosis interventions may support the formation of positive relationships that are comparable to the quality of relationships developed between therapists and clients during face‐to‐face CBT therapy. Methodological limitations including low participant numbers and heightened risk of a Type I error necessitate caution when interpreting findings. Further research into therapist and client variables associated with TA is required. Practitioner points Telephone delivered interventions to support people with psychosis‐related difficulties can result in the development of a good quality TA between therapists and clients. There is a significant difference between therapist and client ratings of TA. Clients tend to score the quality of the TA significantly more highly than therapists. Providing clients with choice when participating in therapeutic interventions could potentially contribute towards improved TA reporting by clients.